Weak geographical structure in sperm morphology across the range of two willow warbler Phylloscopus trochilus subspecies in Scandinavia. (19th April 2016) - Støstad, Hanna N.; Rekdal, Silje L.; Kleven, Oddmund; Laskemoen, Terje; Marthinsen, Gunnhild; Johnsen, Arild; Lifjeld, Jan T.
Abstract : Sperm morphology is highly diversified among species and at higher taxonomic levels. In birds, there is also increasing evidence of geographical differentiation in sperm traits within species, especially in those with strong sperm competition. Geographical divergences in sperm traits might imply the formation of a reproductive barrier in a speciation process. Here we study sperm morphology variation of willow warblers Phylloscopus trochilus in a geographical context in Scandinavia, across the range of two subspecies that are differentiated in certain genetic markers, morphology and migratory routes. We describe geographical patterns in genotypes (two previously described single‐nucleotide polymorphism (SNP) markers and four polymorphic microsatellites); in wing length, tarsus length and body mass; and in sperm traits of 330 male willow warblers sampled at 33 localities across Norway (58°N–69°N). Birds were on average larger and longer‐winged in the north (spp. acredula ) than in the south (spp. trochilus ), and showed a sigmoid change in the SNP allele frequencies and body morphology around 65°N. We found no evidence of genetic structuring in the microsatellites. There was no geographical variation in sperm traits across Norway, except that sperm heads were on average longer in the south. Sperm head length was also associated with the two SNP markers, with longer sperm heads for the southern alleles, and midpiece length was weakly associated with one of the SNP markers. Similar among‐male variances in total sperm length among the 33 sampling sites indicate uniform levels of sperm competition across Norway. We conclude that sperm morphology remains a rather undifferentiated trait between the two willow warbler subspecies in Scandinavia, which is consistent with a pattern of a shallow genetic divergence. This indicates that sperm morphology is not a reproductive barrier maintaining the narrow hybrid zone.